Study of Sodium Benzoat, Cyclamate , Dissolved solids and Water Content on Commercial Product of Jam in Surabaya Region: Kajian Kandungan Natrim Benzoat, Siklamat, Padatan Terlarut, dan Kadar Air pada Produk Selai Komersial di Wilayah Surabaya - Aprilianto, Richardus; Rahmiati, Retnani; Handarini, Kejora (Universitas Muhammadiyah Sidoarjo, 2025)
Jam is a processed food in a gel or semi solid food from fruit pulp with sugar, acid and food additives. Use of food additives with maximum threshold will effect in our body health. Beside of food additives, physical quality characteristics are also important to making the jam. The purpose of this study was to determine value of sodium benzoat, cyclamate, dossolved solids and water content based on merk and various commersial product of jam in Surabaya region. The research method was a descriptive observations with a total of 21 sample tested. The data in this study were analyzed descriptively and inferential statistics. From the research results, were obtained that 14,8% sample exceeds the threshold of sodium benzoat regulation, 61.9% had a little high water content, all of sample followed the regulation in cyclamate threshold and dissolved solids. The result show value of cyclamate was inversely proportional to dissolved solids. Differences in different brands and variants was not significant in the test results of sodium benzoat, cyclamate and water content. While in dissolved solids the brands provided significant different.